CURRENT STATE AND DEVELOPMENT PROSPECTS OF CASHLESS PAYMENTS IN UKRAINE - Rudenko, Z.M. (The actual problems of regional economy development, 2017)
In Ukraine financial sector reform, whose main objective is to reduce cash and expanse cashless payment amount by using modern remote channels, is conducted. The article discusses the theoretical foundations providing of traditional and remote banking services and their main features. Among distance services provided by banking institutions in Ukraine main advantage belongs to Internet banking. Internet banking services were classified on main and additional. The infrastructure of cashless payments in Ukraine and other countries, including the number of ATMs and POS-terminals, the number of cardholders and member banks of card payment systems and banks, with the largest number of issued payment cards in Ukraine, were analyzed. Separately, in the article the remote customer service channels Privatbank and Oschadbank with help leading place in the market system Privat24 and Oschad24 were analyzed. Recommendations for expansion of volume of banks cashless services were given.